Clinical ethics revisited: responses - Benatar, Solomon R (BioMed Central, 2001)
This series of responses was commissioned to accompany the article by Singer et al, which can be found at . If you would like to comment on the article by Singer et al or any of the responses, please email us on editorial@biomedcentral.com.